Experimental investigation of surface modification mechanism in vibratory finishing process - Pradeep Kumar Prakasam (2015)
Vibratory finishing process is a widely used surface modification and polishing process in the aerospace, marine and automotive industry to alter the surface finish. Although it has been used for a long time, the mechanism of the surface modification and the relationship between process parameters and the surface finish obtained is not clear due to the complexity of surface modification mechanism and uncontrollable nature of process parameters. Thus the design of this process for new components is still undertaken on a trial and error basis. Material removal models and optimization algorithms are available for this vibratory finishing, but the type of mechanism which leads to the final surface is still not clear. From a tribological viewpoint, surface modification can be a result of either of two mechanisms – plastic deformation or material removal. This thesis strives to find the effect of process parameters on these mechanisms and final surface obtained. Specialized techniques involving controlled 1D vibration, wear debris analysis and online acoustic emission measurement have been developed. The surface modification mechanism is measured using a novel method and is related to the final surface finish obtained. A novel method to collect the wear debris of the workpiece surface is developed and the wear debris collected is related to the surface modification mechanism and final surface. In 1D vibratory finishing the parallel and perpendicular media motion is separated and the effect of media motion, frequency and amplitude is studied. The contact between the media particles and workpiece are recorded using an acoustic emission sensor and the results are compared. This technique is proposed as an online monitoring technique for vibratory finishing process. The vibratory finishing process is studied and reported from a tribological viewpoint which will be of use to the industries to better understand and optimize the process.